THE LEVEL OF SLEEP QUALITY AMONG UiTM PERLIS STUDENTS DURING POST COVID-19 LOCKDOWN - Noor Hazwanie Mohd Hashim; Zulkifli Ismail; Norfaezah Mohd Rosli; Al Hafiz Abu Bakar (Journal of Islamic, Social, Economics and Development, 2023)
University students’ lifestyles and sleep pattern have changed as a result of the new way of studying that has emerged since COVID-19. Sleep problems and sleep disorders severely impair academic success in university students. There is limited study looking on, level of sleep quality during post COVID-19. Therefore, the purpose of this study is to identify the level of sleep quality among UiTM Perlis student during post COVID-19 lockdown. A total of 437 respondents among UiTM Perlis were distributed through WhatsApp and Telegram applications to answer the questionnaire by Pittsburgh Sleep Quality Index (PSQI) via Google Form. The findings indicate that there are no significant differences in the level of sleep quality among students at UiTM Perlis from seven faculties (p > 0.005). Faculty of Computer Science and Mathematics had a higher mean global score (7.11 ± 3.60). Meanwhile, Faculty of Applied Science had a lower mean global score (6.01 ± 2.90). Overall, the mean global score for all students was (6.57 ± 2.85). According to the findings, none of the seven faculty members have good sleep quality during post COVID-19 lockdown. In conclusion, students at UiTM Perlis have lower levels of sleep quality than average. This can be the outcome of poor sleeping habits, such as an inconsistent sleep schedule.